Tradisi dan Modernitas dalam Perspektif Al-Jabiri; Pemikiran Islam Kontemporer - hadia martanti (TAFAQQUH: Jurnal Hukum Ekonomi Syariah Dan Ahwal Syahsiyah, 2018)
Tradition and modernity about Islamic thought continues to develop along with the style and reality of Islam today, especially in connecting classical Islamic thought and contemporary Islam. One of the Islamic thinkers who sparked the grand dsigen of Arab Islamic thought was Mohammad Abied Al-Jabiri. He is a thinker who also tries to design pragmatic thinking in seeing the Islamic world. The method used in this paper is the descriptive analytic thinking of Mohammad Abied Al-Jabiri by examining several books written directly by the thinker. The results of the study indicate that Al-Jabiri's Islamic thinking strongly emphasizes the epistemology of contemporary Arabic thought as a way to deal with modernity. Al-Jabiri has surpassed ideology in its civilization project, by arranging tetralogy. his serious book was worked on. In his book Nahnu wa At-Turats: Qira'ah Mu'ashirah fi Turatsina al-Falsafi (We and the Heritage of Contemporary Reading to Our Philosophical Heritage), Al-Jabiri maps procedural differences between ideologically charged thoughts and epistemological Arabic philosophy. According to Al-Jabiri, the epistemological content of Arab-Islamic philosophy, namely science and metaphysics has an intellectual world different from its ideological content, because the second charge is related to socio-political conflict when it is built. Both terms (epistemological-ideological) are often used by Al-Jabiry in his study of Arabic Intellect. The term epistemology is a collection of thought rules that are ready to be used in various social conditions. Meanwhile, the term ideology is a social and political condition that influences the direction of thinking of each character in the time and place where he is